MODEL FOR EVALUATING THE DEGREE OF INVESTMENT ATTRACTIVENESS OF IT-PROJECTS - Lutskyi, Maksym; Sydorenko, Viktoriia; Yarotskiy, Stanislav (Science-based technologies, 2023)
Attracting foreign direct investment in the development of post-war Ukraine is impossible without a complete, justified and comprehensive analysis of the degree of investment attractiveness (DIA) of the relevant industrial and infrastructure facilities. Moreover, it is clear that the specified analysis should be based on modern expert system and information technologies and classical decision-making criteria (CDMC). Therefore, today, more than ever, issues of development and implementation of projects in the IT sphere, training of IT personnel, creation and evaluation of attractive conditions for investments are becoming more relevant. The paper is devoted to the development of expert technologies for the construction and analysis of group preference systems (GPS) of experts on a set of characteristic features of investment attractiveness (CFIA) for evaluating DIA IT projects. The system of DIA’s advantages is understood as a reasonable ordering (ranking) of these features: from more acceptable, significant, weighty, etc., to less acceptable. DIA evaluation model of IT projects has been developed, which, using the construction of decision matrices on a set of CFIAs and a comprehensive comparative analysis of all received GPS, allows for the selection of the optimally effective CDMC for DIA evaluation of IT projects at an unusually high significance level of a=1%. And the conducted experimental study of the proposed DIA evaluation model of IT projects established, in relation to other CDMCs, the effectiveness of the Savage criterion, since it has an optimization content, that is, it minimizes deviations in GPS in the opinions of both the majority and the minority of the tested. It resulted in the maximum generalized GPS match value that was constructed using other CDMC methods. However, on the other hand, in the CDMC, Savage influenced the appearance of related ranks in the GPS. In addition, the need for an in-depth study of the attitude of the members of the mC subgroup as the most numerous, and therefore reliable, to the significance of the features of the investment attractiveness of the examination objects is substantiated.